Histomorphometric Assessment of Vibrational Forces on the Extended Midpalatal Suture - Pasaoglu Bozkurt, Aylin; Özdal Zincir, Özge; Emincik, Asli (Journal of Dentistry Indonesia, 2024)
Objective: This study determined the effects of vibrational forces on bone formation in the retention period of an expanded mid-palatal, histomorphometric suture in a rat model. Methods: Twenty-four 7–8- to 8-week-old male Wistar rats weighing 190.25 ± 15.35 g were separated into groups: only expansion (G1), expansion and 30 Hz vibration application (G2), and expansion and 111 Hz vibration application (G3). After 5 days of expansion, there were 12 days of retention. All animals were sacrificed, and their premaxilla were dissected. A histological examination evaluated the number of osteoblasts, osteoclasts, and capillaries, the amount of mineralized area, and the fibrosis area. Results: Statistical analyses showed significant differences among the groups for all parameters. The number of osteoblasts, new bone area, fibrosis area, blood vessels, and measurements demonstrated statistically significant differences. For all histomorphometric parameters except osteoclast numbers, G3 showed more positive results than G1 and G2 regarding new bone formation (p < 0.05). Conclusion: The application of vibrational forces might stimulate bone formation in an orthopedically expanded midpalatal suture during the retention period. These applications may help prevent relapse after the expansion procedure.